Large scale implementation of effective early literacy instruction - Gillon, Gail; McNeill, Brigid; Scott, Amy; Gath, Megan; Macfarlane, Angus; Taleni, Tufulasi (Frontiers in Education, 2024)
Introduction Large-scale implementation of Multi-Tiered Systems of Support (MTSS) to enhance children's early literacy success is critically important to address global literacy challenges. This paper describes one such initiative, the Better Start Literacy Approach (BSLA), which was specifically designed for large-scale implementation in New Zealand. Methods Between February 2020 and May 2023 over 3,000 teachers in 819 schools across New Zealand implemented BSLA, with baseline data available for 29,795 5-year-old children. Teachers implemented novel online assessments to monitor children's early literacy growth. Results In comparison to an internal control group, accelerated progress in children's phonic, and phoneme awareness skills was evident after 10 weeks of BSLA Tier 1 (universal) teaching. After 30 weeks, there were significant gains in word reading, spelling, listening comprehension and oral narrative abilities; growth did not differ based on gender, ethnicity, or socioeconomic status. Children with greater learning needs who received BSLA Tier 2 (small group targeted teaching) caught up to their peers in word reading and spelling skills. Conclusions With appropriate resourcing, planning and engagement with communities, successful large-scale implementation of evidenced-based early literacy approaches is possible within a relatively short time. Culturally responsive implementation within MTSS frameworks holds much promise for raising literacy achievement for all children.